2020–2021 Vegetable Production Handbook: Chapter 3. Principles and Practices of Irrigation Management for Vegetables - Lincoln Zotarelli; Michael D. Dukes; Eric H. Simonne; Charles E. Barrett; Peter Dittmar (EDIS)
This section contains basic information on vegetable water use and irrigation management, along with some references on irrigation systems.